Multiple functions and regulatory network of miR-150 in B lymphocyte-related diseases - Hu, Yue-Zi; Li, Qiao; Wang, Peng-Fei; Li, Xue-Ping; Hu, Zhao-Lan (Frontiers in Oncology, 2023)
MicroRNAs (miRNAs) play vital roles in the post-transcriptional regulation of gene expression. Previous studies have shown that miR-150 is a crucial regulator of B cell proliferation, differentiation, metabolism, and apoptosis. miR-150 regulates the immune homeostasis during the development of obesity and is aberrantly expressed in multiple B-cell-related malignant tumors. Additionally, the altered expression of MIR-150 is a diagnostic biomarker of various autoimmune diseases. Furthermore, exosome-derived miR-150 is considered as prognostic tool in B cell lymphoma, autoimmune diseases and immune-mediated disorders, suggesting miR-150 plays a vital role in disease onset and progression. In this review, we summarized the miR-150-dependent regulation of B cell function in B cell-related immune diseases.